The expression 4x - 4x simplifies to 0. This is because when you subtract 4x from 4x, you are essentially subtracting an equal value from itself, resulting in a net change of zero. In algebra, this type of simplification is known as combining like terms, where terms with the same variable and exponent are added or subtracted.
5x - 4x = x
x - 2
The expression "x minus 4x" can be simplified by combining like terms. When subtracting 4x from x, we are essentially subtracting 4 of the x terms from 1 of the x terms, resulting in a final answer of -3x. So, x minus 4x simplifies to -3x.
Would you mind typing it out for me? I don't quite understand exactly what you are asking. For example, x to the second power minus 4x over x to the second power minus 16 would be... x^2-4x/x^2-16 Do you mind typing it out like that? Because what you wrote makes no sense at all.
(2x - 1)(2x + 1)
4x + 20
5x - 4x = x
3x - 12 = 10x - 15 - 6x -10 3x - 12 = 4x -25 3x + 13 = 4x 13 = 4x - 3x 13 = x None?
(4x-5)(4x+5)
x2 - 4x - 21 = (x-7)(x+3)
-14x
7x2 -4x -5x2 +2x = 2x2 -2x
(2x-1)(2x-1) = 4x^2 -4x + 1
Let 6x - 2x - 9 = a, where a is an arbitrary constant. Then 4x - 9 = a 4x = a+9 x = (a+9)/4
x(4x-2)
6x - 4y
It is possible.